Analisis Putusan Nomor 1/Pid.Sus/2023/PT Bandung Tentang Affiliator Trading Forex DS Perspektif Hukum Pidana Islam - Rizkiansyah, Aprila; Najmudin, Deden; Azazy, Yusuf (Universitas Cokroaminoto Yogyakarta, 2025)
This study analyzes the court decision in the DS case concerning fraud who have disseminated false information, resulting in losses for thousands of people from the perspective of Islamic criminal law. The research employs a normative juridical method, referencing books, journals, and legal rulings. Money laundering offenses are regulated by Law No. 8 of 2010 to protect the national financial system. The Bandung High Court Decision No. 1/Pid.sus/2023/PT Bdg sentenced DS to eight years of imprisonment, an increase from the first-instance court's, and mandated restitution for the victims. Under Islamic criminal law, the defendant's actions can be analyzed through the concepts of gharar (uncertainty) and khilda (fraud), with ta'zir punishments imposed at the discretion of the judge. This case underscores the importance of fair law enforcement, the protection of society, and alignment with Islamic legal norms in addressing harmful actions.